Book review: Foundation of Islamic governance: a Southeast Asian perspective. - Fontaine, Rodrigue Ancelot Harvey (Universiti Sains Malaysia, 2018)
This is a book review of Dr Maszlee Malik's (2017) Foundation of Islamic governance: A Southeast Asian perspective.published by Routledge.